Internal Astigmatism and Its Role in the Growth of Axial Length in School-Age Children - Liangcheng Wu; Chenghai Weng; Fei Xia; Xiaoying Wang; Xingtao Zhou (Journal of Ophthalmology)
Objectives. To explore the role of internal astigmatism (IA) in the growth of axial length (AL) in school-age children. Methods. Total astigmatism (TA), corneal astigmatism (CA), and AL of all children in Jing’an District 2nd Centre Primary School in Shanghai were measured. In IA, the difference between TA and CA was also calculated using vector analysis. The association of axial length with IA, genders, and age was analyzed using linear regression. The difference of IA between both eyes was also calculated. The AL between both eyes was compared using paired samples t-test when DIA = 0 D, <0.5 D, and ≥0.5 D. Results. Six hundred and twelve cases (98.23%) in 623 children aged 7–12 yrs older entered into the study. Genders, age, and IA all affected AL. This could be represented by a linear regression line in the form AL = 21.46 − 0.43∗gender + 0.22∗age + 0.46∗IA (male = 1, female = 2; t=7.01, P<0.01 for sex; t=11.6, P<0.01 for age; and t=6.6, P<0.01 for IA; R2=0.16). The AL in the eye with larger IA was also longer when DIA was larger than 0.5 D (t=2.65, P<0.01). Conclusions. IA was observed to be associated with AL and might be a risk factor of the onset and progress of myopia in school-age children.